Two-component system GrpP/GrpQ promotes pathogenicity of uropathogenic Escherichia coli CFT073 by upregulating type 1 fimbria - Xueping Li; Yu Pang; Lingyan Jiang; Le Liu; Jiarui Zhou; Chen Jin; Qian Wang; Hongmin Sun; Qing Li; Zhen Chen; Jingliang Qin; Jianwei Mu; et al. (Nature Communications)
Abstract Uropathogenic Escherichia coli (UPEC) is a major cause of urinary tract infections (UTIs). Invasion into bladder epithelial cells (BECs) on the bladder luminal surface via type 1 fimbria is the first critical step in UPEC infection. Although type 1 fimbria expression increases during UPEC invasion of BECs, the underlying regulatory mechanisms remain poorly understood. This study reported a previously uncharacterized two-component system (TCS) GrpP/GrpQ that directly activates type 1 fimbria expression to promote UPEC invasion and therefore pathogenicity in response to D-serine present in the host urine. grpP/grpQ mutation severely impaired UPEC invasion of BECs and decreased the bacterial burden and formation of intracellular bacterial communities in mouse bladders during acute UTI. grpP/grpQ is widely present in UPEC genomes but rarely in other E. coli genomes, suggesting that this TCS specifically contributes to UPEC evolution. This study revealed a new pathway for virulence activation in response to host cues, providing further insight into UPEC pathogenesis and a promising target for UTI treatment.